Revisiting Reuter: Symbolic and material economies in Bali aga society - Alexander R. Cuthbert; G.A.M. Suartika (Universitas Udayana, 2017)
The objective of this paper is to analyse Thomas Reuter’s seminal text The Custodians of the Sacred Mountains and to discuss some of the theoretical and other issues that flow from the reading. Indirectly it is also intended to assist many local scholars who find the text somewhat impenetrable, let alone making connections to its extensive implications. The book is the second study to emerge that covers the regional basis for the Bali Aga, the first being that of Wälty (1997). The text is one of a kind - erudite, complex and intellectually challenging. The paper begins with historical interventions since the status economy of Bali Aga is wholly dependent on a mythical past. Next, the use of theory, focussing on anthropology and Bali studies is discussed to place Reuter’s work in context. Then his basic concepts are analysed, those of precedence, status, and representation. Subsequently, we focus on place and space since geography is a defining feature of Bali Aga. Finally the mental (symbolic) and material (political economy) dimensions are contrasted with the observation that omission of any consideration of the latter weakens an otherwise seminal work.